Managing Risk and Information Security: Protect to Enable (Second Edition) - Malcolm W. Harkins (Apress, 2016)
Examine the evolving enterprise security landscape and discover how to manage and survive risk. While based primarily on the author's experience and insights at major companies where he has served as CISO and CSPO, the book also includes many examples from other well-known companies and provides guidance for a management-level audience. Managing Risk and Information Security provides thought leadership in the increasingly important area of enterprise information risk and security. It describes the changing risk environment and why a fresh approach to information security is needed. Because almost every aspect of an enterprise is now dependent on technology not only for internal operations but increasing as a part of product or service creation, the focus of IT security must shift from locking down assets to enabling the business while managing and surviving risk. This edition discusses business risk from a broader perspective, including privacy and regulatory considerations. It describes the increasing number of threats and vulnerabilities and offers strategies for developing solutions. These include discussions of how enterprises can take advantage of new and emerging technologies-such as social media and the huge proliferation of Internet-enabled devices-while minimizing risk. What You'll Learn Review how people perceive risk and the effects it has on information security See why different perceptions of risk within an organization matters Understand and reconcile these differing risk views Gain insights into how to safely enable the use of new technologies Who This Book Is For The primary audience is CIOs and other IT leaders, CISOs and other information security leaders, IT auditors, and other leaders of corporate governance and risk functions. The secondary audience is CEOs, board members, privacy professionals, and less senior-level information security and risk professionals.